Exposição ao ruído ocupacional entre profissionais de saúde bucal de um serviço odontológico universitário - Oliveira, Germano de (2022)
Introduction: A health and safety program at work objective identify situations that can affect the physical and mental integrity of workers. In between workers who suffer the influence of occupational noise are dental professionals. In Brazil, the main standards that address these risks are the Occupational Hygiene Standard Nº. 01 (NHO, 2001) and Regulatory Standard Nº. 15 (NR 15, 1978), which establish criteria for exposure to occupational noise, defining the tolerance limits in environments in unhealthy activities. In this dissertation, the report of the results and the discussion were presented in the form of two articles: the first fits into the category of systematic review of the literature on occupational noise in dental work, and the second is an original article, with a report of field research, based on an applied investigation on the exposure of dental professionals in the oral health unit of a university hospital. Objectives: The general objective was to evaluate evidence from the scientific literature, focusing on the occupational exposure of dental teams to noise in the work environment, as well as whether this exposure represents a risk for professionals at the Oral Health Unit of the University Hospital Lauro Wanderley HULW), in João Pessoa, Paraíba. Methods: In the first study, a systematic review was carried out using the SciELO, LILACS, MEDLINE, Scopus and Web of Science databases. The descriptors used were those indexed in DeCS (Descriptors in Health Sciences) and in MeSH (Medical Subject Headings), among which the following stand out: Noise AND Occupational AND Dentistry. All of them were searched considering works produced and published in Portuguese, English and Spanish. The second study - observational and cross-sectional - was carried out at the Oral Health Unit (USB) of the HULW. The primary variable consisted of noise dosimetry measurements, using electronic devices to measure the exposure of USB professionals during eight hours of work. The secondary variables were sociodemographic, with the participants' self-report about symptoms related to hearing damage suffered and about their subjective appreciation of the sources of greater noise in the work environment. Results: In the review, the articles included showed conflicting findings in relation to the noise levels observed within the tolerance limits and the results that detected risk of hearing impairment of exposed professionals. In the field study, however, the values observed in the dosimetry revealed that the professionals were exposed to noise levels within the eight-hour tolerance limit. The estimated mean values for NHO 01 and NR 15 were, respectively, 74.46 dB(A) and 66.17 dB(A), with standard deviations of 3.18 dB(A) and 4.43 dB(A). In addition, the values of the coefficients of variation for these measures were 4.27% and 6.70%, respectively. Conclusions: The scientific production on occupational noise in the dental field in the last ten years is limited, due to the small number of descriptive studies and low level of scientific evidence, demanding the need for more empirical research. In the field study, the results revealed that the noise intensities of the evaluated environment are in accordance with Brazilian regulatory standards.